Exposure to Per- and Polyfluoroalkyl Substances and Risk of Psoriasis: A Population-Based Study - Qing Zhang; Mengyue Zhang; Cunxi Zhao (Toxics)
PFAS are a group of synthetic chemicals that have been reported to be associated with adverse health outcomes. However, the relationship of PFAS exposure with psoriasis risk has not been reported. Utilizing data from the 2003–2018 NHANES, we explored the relationship of PFAS exposure with psoriasis risk. Our study included 5370 participants and examined serum levels of five PFAS compounds: PFOA, PFOS, PFHxS, PFNA, and PFDA, along with self-reported psoriasis status. Generalized linear regression, quantile g-computation, repeated hold out WQS regression, and BKMR models were employed to assess individual and combined effects of PFAS on psoriasis risk. We found each doubling the PFOS concentration was associated with a 19% increased risk of psoriasis (OR: 1.19; 95% CI: 1.01, 1.41) in the overall population. Sex-stratified analyses indicated significant associations between PFOA and PFNA exposure and psoriasis risk in females. Mixture analyses using WQS regression indicated that PFAS mixtures were associated with an 11% increased risk of psoriasis (OR: 1.11, 95% CI: 1.01, 1.22) in females in both the negative and positive direction. BKMR analyses also indicated a positive trend of PFAS mixtures with psoriasis risk in females. Our findings indicate a possible association between PFAS exposure and psoriasis risk, particularly in females.